2008
DOI: 10.1016/j.ejvs.2007.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Association Studies in Abdominal Aortic Aneurysm Disease: A Review and Meta-Analysis

Abstract: Three of these polymorphisms were associated with a significant risk of AAA, ACE RR 1.33 [95% CI 1.20-1.48], MTHFR RR 1.14 [1.08-1.21] and MMP9 RR 1.09 [1.01-1.18]. These differences have been previously reported as equivocal, within a context of contradictory studies and as such this meta-analysis provides new evidence for their involvement in AAA disease. The plausibility of these findings is discussed within the context of a systems approach to the pathology of AAA disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 61 publications
2
69
0
Order By: Relevance
“…A common polymorphism (G994T) in this gene reduces enzyme activity and results in increased levels of PAF. A significant association with the T-allele and AAA has been demonstrated (Thompson et al, 2008).…”
Section: Tissue Inhibitors Of Mmp's and Plasminogen Activator Inhibitorsmentioning
confidence: 95%
See 4 more Smart Citations
“…A common polymorphism (G994T) in this gene reduces enzyme activity and results in increased levels of PAF. A significant association with the T-allele and AAA has been demonstrated (Thompson et al, 2008).…”
Section: Tissue Inhibitors Of Mmp's and Plasminogen Activator Inhibitorsmentioning
confidence: 95%
“…Several studies have investigated the link between MTHFR gene polymorphisms and AAA (Brunelli et al, 2000;Jones et al, 2002;Strauss et al, 2003;Ferrara et al, 2006). All but one of these demonstrated a link between the T allele polymorphism and AAA, a meta-analysis of these studies confirmed a significant effect in favour of the T-allele variant increasing the risk of AAA (Thompson et al, 2008). Interestingly, the study that did not provide evidence to suggest a link between the T-allele and AAA, did suggest that it may be a contributory factor in AAA severity as indicated by aneurysm size (Strauss et al, 2003).…”
Section: Mthfr Genementioning
confidence: 99%
See 3 more Smart Citations